2016
DOI: 10.1002/adma.201601413
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Singlet Oxygen Generation in Oxidized Graphitic Carbon Nitride for Organic Synthesis

Abstract: Experimental data reveal that the incorporation of carbonyl groups into polymer matrix can significantly enhance singlet oxygen ((1) O2 ) generation and suppress production of other reactive oxygen species. Excitonic processes investigated by phosphorescence spectroscopy reveal enhanced triplet-exciton generation in the modified g-C3 N4 , which facilitate (1) O2 generation through an energy transfer process. Benefiting from this, the modified g-C3 N4 shows excellent conversion and selectivity in organic synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
315
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 445 publications
(333 citation statements)
references
References 35 publications
13
315
1
4
Order By: Relevance
“…The other three peaks at 286.81, 288.94 and 293.51 eV were attributed to C−O, C=O and C−NH 2 bonds, respectively . The presence of C−O and C=O bonds confirmed the initial assumption from the EDS spectra that g‐C 3 N 4 was oxygen functionalized . The N 1s spectrum (Figure b) contained four peaks at 398.35, 399, 400.87 and 404.19 eV.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other three peaks at 286.81, 288.94 and 293.51 eV were attributed to C−O, C=O and C−NH 2 bonds, respectively . The presence of C−O and C=O bonds confirmed the initial assumption from the EDS spectra that g‐C 3 N 4 was oxygen functionalized . The N 1s spectrum (Figure b) contained four peaks at 398.35, 399, 400.87 and 404.19 eV.…”
Section: Resultsmentioning
confidence: 99%
“…[27,28] The presence of CÀOa nd C=Ob onds confirmed the initial assumption from the EDS spectra that g-C 3 N 4 was oxygen functionalized. [29][30][31] The N1ss pectrum( Figure 4b) contained four peaks at 398.35, 399, 400.87 and4 04.19 eV.T he main peak at 398.35eVw as attributedt os p 2 -hybridized nitrogen in the aromatic ring (C=NÀC), whereas the peaks at 399 and 400.87 eV were attributed to sp 3 -hybridized N-C 3 and C-N-Hg roups in the g-C 3 N 4.…”
Section: Resultsmentioning
confidence: 99%
“…The PF and PH emissions were found to peak at 452 and 496 nm, respectively, suggesting a singlet–triplet energy gap of ∼0.243 eV, in accordance with our previous report. 19 The tiny discrepancy is inevitable due to a few differences in the details of preparation for the two papers. Temperature-dependent fluorescence spectra suggest a significant enhanced emission at low temperature (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently we demonstrated the existence of singlet and triplet excitons in g-C 3 N 4 and found that the involved excitonic processes can be effectively regulated by the incorporation of carbonyl groups, thereby facilitating the generation of triplet excitons and enhancing the production of singlet oxygen. 19 The intriguing excitonic-effects-dominated photocatalytic molecular oxygen activation behavior in polymeric carbon nitride inspires us to further pursue excitonic aspects in polymeric photocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…TheXRD pattern of as-prepared g-C 3 N 4 in Figure 2c displays two typical (100) and (002) diffraction peaks,providing asolid evidence for the successful formation of g-C 3 N 4 .The C/N molar ratio is close to the theoretical value of about 0.75, determined by X-ray photoelectron spectroscopy (XPS) and elemental combustion analysis (Supporting Information, Figure S2). [12,13] To fabricate an effective Schottky junction (Figure 1), the proportional quantities of both samples were mixed and ground. [12,13] To fabricate an effective Schottky junction (Figure 1), the proportional quantities of both samples were mixed and ground.…”
mentioning
confidence: 99%